The Influence of Organization Capability On Preventive Maintenance Practices and SMEs Performance in Malaysia - Che Azlan bin Taib; Halim Mad Lazim; Hendrik Lamsali; Mohamed Najib Saleh; Chandrakantan Subramaniam (International Journal of Supply Chain Management, 2017)
Preventive Maintenance (PM) is one of the key approaches towards realizing the goal of organization performance. Hence, it is extensively applied and become an important aspect in the manufacturing sectors. PM plays a pivotal role to avoid potential stoppages and disruptions of equipment from occurring in daily operations. PM utilizes total employee involvement in the maintenance activities to avoid potential disruptions, breakdowns, stoppages, and failures. Despite the sector contribution to the Malaysia economy for which the Small Medium Enterprises (SMEs) makes up 95% of the total manufacturers, preventive maintenance practices remain relatively lacking. In the highly competitive manufacturing industries, the ability and reliability of equipment is very important in order to achieve desired manufacturing performance. However, empirical evidence on the potential impact of PM practices towards manufacturing performance remains limited and indecisive. For Small Medium Enterprises (SMEs), the extent of how organizational capability influences manufacturing performance is also inconclusive. Henceforth, this study aims to investigate potential relationships between PM practices and manufacturing performance moderated by organizational capability with a focus on Malaysian SMEs. The study is intended to put forward a new framework and hypotheses to examine the above mentioned relationships. The proposed framework includes PM team, PM strategy and planned maintenance as the independent determinants, while organizational capability serves as the moderating variable. At the other end, measurement for manufacturing performance comprises of innovation and financial factor is considered. Research direction and conclusion are then discussed at the end of the study.